Field reports form for submitting seasonal observations of Iowa birds, Jan L. Walter, fall 1992 - Walter, Jan L.et al (1992)
Fall report of birds found in northern Iowa contributed by Jan L. Walter. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1992. Plustek - flatbed